2017
DOI: 10.1159/000475599
|View full text |Cite
|
Sign up to set email alerts
|

Osthole, a Coumadin Analog from <b><i>Cnidium monnieri</i></b> (L.) Cusson, Ameliorates Nucleus Pulposus-Induced Radicular Inflammatory Pain by Inhibiting the Activation of Extracellular Signal-Regulated Kinase in Rats

Abstract: Aim: This study was aimed at assessing the role of extracellular signal regulated kinase (ERK) in mechanical allodynia resulting from lumbar disc herniation (LDH) and exploring the osthole's anti-nociceptive effect on ERK activation. Methods: Radicular pain was generated by applying nucleus pulposus (NP) to the L5 dorsal root ganglion (DRG). Allodynia was measured using Von Frey filaments to calculate the mechanical pain threshold. Phosphorylated ERK and total ERK protein in the lumbar spinal dorsal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Osthole, a natural coumarin extract from the fruit of Cnidium monnieri (L.) [ 21 ], has several beneficial pharmacological properties, such as antiseizure [ 22 ], antiosteoporosis [ 23 ], and antitumour [ 24 ] activities. Recently, studies found that osthole attenuates chronic kidney failure by inhibition of inflammation [ 25 ]. It also suppresses acute inflammatory responses in acute mechanical brain injury and kidney injury [ 26 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Osthole, a natural coumarin extract from the fruit of Cnidium monnieri (L.) [ 21 ], has several beneficial pharmacological properties, such as antiseizure [ 22 ], antiosteoporosis [ 23 ], and antitumour [ 24 ] activities. Recently, studies found that osthole attenuates chronic kidney failure by inhibition of inflammation [ 25 ]. It also suppresses acute inflammatory responses in acute mechanical brain injury and kidney injury [ 26 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Paeonol inhibits the production of NO, PGE2, and IL-6 induced by LPS via prevention of ERK activation in RAW264.7 macrophages. Meanwhile, paeonol decreased protein expression of iNOS and COX-2 and production of pro-inflammatory cytokines, such as TNF-α and IL-1β, NO and PGE2, and increased production of IL-10 in rat paw exudates of rat model of carrageenan-evoked thermal hyperalgesia (50,79).…”
Section: Affect Purinergic Receptorsmentioning
confidence: 99%
“…The various classes of flavonoids differ in the level of oxidation and the pattern of substitution of the C ring, whereas individual compounds within a class differ in the pattern of substitution of the A and B rings (11). Flavonoids (41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55) in TCM play an important role in analgesia, and have high application value and prospect.…”
Section: Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fructus Cnidii is the dried ripe fruit of Cnidium monnieri (L.) Cuss. with some pharmacological effects, such as sedative effect [8], hypnotic action [8], anti-nociceptive effect [9], anti-cancer [10], and anti-inflammation [11]. Radix Glycyrrhizae is the dried root and rhizome of Glycyrrhiza uralensis Fisch., Glycyrrhiza inflata Bat.…”
mentioning
confidence: 99%